Organotemplate-free hydrothermal synthesis of NaNKX-2 aluminophosphite basic catalyst - Gopal, L.; Lim, G.K.; Ling, T.C.; Adnan, R.; Juan, J.C.; Ng, E.P. (Elsevier, 2016)
NaNKX-2 aluminophosphite crystals were synthesized for the first time in the Al2O3–P2O5–Na2O–H2O system without anok y organic additive. The NaNKX-2 crystals were obtained under autogeneous condition within 4 h, which was considerably fast and convenient. The study revealed that the use of basic synthesis condition and H3PO3 as the phosphorus source were the crucial factors in obtaining NaNKX-2 crystals. The NaNKX-2 crystals, which exhibited novel grain-like morphology, had a P:Al:Na ratio of 4:3:1.7. The potential of NaNKX-2 as a catalyst in basic-catalyzed cyanoethylation of methanol was also demonstrated.